Minyak ikan Lemuru (Sardinella longicep) menurunkan apoptosis osteoblas pada tulang alveolaris tikus wistar (Fish oil of Lemuru (Sardinella longicep) reduced the osteoblast apoptosis in wistar rat alveolar bone) - Didin Erma Indahyani (Universitas Airlangga, 2013)
Background: Periodontal disease is caused by periodontopatogen bacteria resulting the alveolar bone damage. The decrease of osteoblasts and the increased of osteoclasts can cause bone destruction. The decrease of osteoblasts, due to a disturbance of differentiation, proliferation and apoptosis. Inflammatory mediators are prostaglandin E2 (PGE2), interleukin-1 (IL-1), IL-6 also tumor necrosis alpha (TNF-α) stimulates osteoblast apoptosis through gene expression, signaling molecules and receptor-forming osteoblasts. Fish oil of Lemuru, which is widely encountered in Indonesian coast, containing n-3 poly unsaturated fatty acids (n-3 PUFAs) are quite high. Consumption of fish oil shown to reduce the expression of PGE2, IL-1, IL-6 and TNF-α. Purpose: The purpose of this study was to examine the effect of Lemuru (Sardinella longicep) fish oil on osteoblast apoptosis of rat alveolar bone induced periodontal infection. Methods: Thirty Wistar rats, male, age 5 days, divided into 3 groups: group I rats induced with normal saline, group II rats induced by LPS, and group III rats induced with lemuru fish oil and LPS. Each group was divided into 2 sub-groups that would be sacrified at 13 days and 21 days of age. Fish oil was given at a dose 1ml/300-350 grams. Lipopolysaccharide (LPS) induced with the purpose to cause periodontal infection in the maxillary buccal fold molar region with dose 5μl LPS/PBS 0.03 ml. After decapitation and decalcification, the maxilla was cut in 5μm thickness. Apoptosis was analyzed on DNA and detected by TUNEL reaction (transferase-mediated digoxigenin-deoxy-UTP nick end labeling). Results: The results showed that apoptosis of osteoblast cells was significantly smaller in rats induced by Lemuru fish oil. Conclusion: The study showed that Lemuru fish oil reduced the osteoblast apoptosis of rats alveolar bone induced periodontal infection by LPS. <span style="font-family: Tribune-Italic; font-size: 9pt; color: